2008
DOI: 10.2174/1874848100801010020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Improvement of Active Tuberculosis Patients with Complex Treatment and Nutritional Supplementation

Abstract: Global incidence of tuberculosis, especially multiple-drug resistant tuberculosis, has been increasing, despite development and use of various antimicrobial drugs for decades, leading to 2 million deaths a year. We evaluated the effect of micronutrient supplementation as an adjunct to standard treatment of patients with active pulmonary tuberculosis, on clinical improvement and frequency of adverse events on 120 patients aged 20 to 65 years diagnosed with active pulmonary tuberculosis at the Kiev Department of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Previous studies observed that vitamin E was significantly depleted in tuberculosis patients when compared with healthy individuals [21] , [37] . Administration of micronutrients, including vitamin E, has been shown to enhance antioxidant status [35] and accelerate tuberculosis healing [38] . Vitamin E presumably will also give benefit to tuberculosis patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies observed that vitamin E was significantly depleted in tuberculosis patients when compared with healthy individuals [21] , [37] . Administration of micronutrients, including vitamin E, has been shown to enhance antioxidant status [35] and accelerate tuberculosis healing [38] . Vitamin E presumably will also give benefit to tuberculosis patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…These deficits include: (i) specific micronutrient abnormalities such as reduced blood levels of the common ACE vitamins, minerals, trace elements including selenium, amino acids such as cysteine, and the tri-peptide glutathione, which displays a global systemic deficiency; (ii) macronutrient abnormalities such as protein calorie malnutrition, which has been linked to a wasting disease, characteristic of AIDS. Malnutrition has also been linked to the spread of AIDS and TB in developing countries and with reduced survival (Paton et al, 2006, Turchenko et al, 2008 MICRONUTRIENT ABNORMALITIES…”
Section: Nutritional Deficiencies In Hiv and Aidsmentioning
confidence: 99%